The technical development of forwarders in Sweden between 1962 and 2012 and of sales between 1975 and 2017. Issue 1 (2nd January 2019) - Nordfjell, Tomas; Öhman, Emil; Lindroos, Ola; Ager, Bengt
ABSTRACT: Although being rather similar in appearance, forwarders have gone through substantial development during the more than half a century they have been used in forestry. The aim was to describe the development in Sweden, by a combination of historical narratives and data. The latter consists of technical parameters of forwarders sold on the Swedish market from 1962 to 2012, together with sales figures from 1975 to 2017. Data were collected from the original specifications from manufacturers; advertisements in old forestry magazines; Internet forums; and from the literature. In total, 51 forwarder manufacturing companies were identified, all located in Sweden or Finland, which produced over that time 361 models in total. The weight and load capacity has increased over time, as well as engine power and torque per tonne total weight. Load index has decreased over time. Ground pressure decreased from 1962 to 1985, but then remained stable. In Sweden, 12, 602 forwarders were sold from 1975 to 2012. The trend for annual sales decreased until 1993 but since 2005 has increased to between 300 and 400 forwarders per year. Since 1995 annual sales in Sweden have been between four and six forwarders per million m 3 harvested industrial wood. Corresponding values for the years 1975–1984 were double that. Why the first Swedish forwarder was developed from a farm tractor rather than importing an already existing, purpose-built forwarder from Canada is discussed, as well as the probable direction of future developments in forwarder design and construction. New forwarder size-classes are suggested. Soil damage issues are predicted to be of increased importance.